2021
DOI: 10.3390/separations8050062
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI-QTOF-MS/MS Profiling and Antioxidant Activity of Phenolics from Custard Apple Fruit and By-Products

Abstract: Custard apple is an edible fruit grown in tropical and subtropical regions. Due to its abundant nutrient content and perceived health benefits, it is a popular food for consumption and is utilized as a medicinal aid. Although some published research had provided the phenolic compound of custard apple, the comprehensive phenolic profiling of Australian grown custard apple is limited. Hence, this research aimed to evaluate the phenolic content and antioxidant potential by various phenolic content and antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 75 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…Previous studies have shown the FICA of sweet cherry as 24.90 as IC 50. 41 The FICA values of custard apples were reported from 0.13 ± 0.01 to 2.17 ± 0.19 mg EDTA/g, 38 which shows a wider range of values than sweet cherries. Thus, the metal chelating abilities of sweet cherries might be similar to custard apples.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have shown the FICA of sweet cherry as 24.90 as IC 50. 41 The FICA values of custard apples were reported from 0.13 ± 0.01 to 2.17 ± 0.19 mg EDTA/g, 38 which shows a wider range of values than sweet cherries. Thus, the metal chelating abilities of sweet cherries might be similar to custard apples.…”
Section: Resultsmentioning
confidence: 98%
“…Vinitha et al studied the RPA activity of sweet cherry in India but recorded their results in the form of dry weight. The RPA values of custard apples were reported to be 1.24 ± 0.12–6.47 ± 0.03 mg AAE/g in fresh weight, which showed a higher value than sweet cherries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• OH-RSA and FICA assays. Previously, a thorough phenolic analysis of custard apples cultivated in Australia has been performed by Du et al [60]. They found that African Pride peel possessed the greatest antioxidant capacity for RPA (5.32 ± 0.14 mg AAE/g),…”
Section: Antioxidant Capacity Of Bananamentioning
confidence: 99%